PENERAPAN PASAL 5 AYAT (1) Undang-Undang NOMOR 8 TAHUN 2010 TENTANG TINDAK PIDANA PENCUCIAN UANG TERHADAP NOTARIS YANG MELAKUKAN PENCUCIAN UANG - Budiman, Maman (Faculty of Law, Universitas Pasundan, 2023)
The act of money laundering committed by a Notary begins with a conspiracy with his client. The conspiracy is due to alleged criminal acts such as corruption. The problems in this paper are the factors that cause Notaries to commit money laundering, whether Article 5 Paragraph (1) of Law Number 8, 2010 can be applied to Notaries who commit money laundering and the obstacles faced by law enforcement officials when processing Notaries who commit such offense. The research in this paper uses normative legal methods by examining document studies, using various secondary data such as laws and regulations, court decisions that have permanent legal force, legal theories, and expert opinions. The analysis is qualitative. The factors that cause the Notary to do this are intentional to protect the assets of their clients, the lifestyle of Notaries who want to get instant wealth through illegal means. The imposition of Article 5 Paragraph (1) of Law Number 8 of 2010 against a Notary who is suspected of committing the crime of money laundering requires proof of its origin and the obstacles faced by law enforcement officials in processing Notaries who commit the crime of money laundering. Keywords: Notary, Criminal Act, Money Laundering.